Responding to rural health disparities in the United States - Ian Jones; David López-Carr; Pamela Dalal (Netcom)
The paper focuses on the need to address territorial inequalities in American healthcare services. It shows how much the situation has become critical in the United States. It discusses to what extent telemedicine is a sustainable option to reduce the negative consequences of the economic, professional and physical barriers to care in rural areas. As far as healthcare is concerned, rural and urban environments in the United States do not have to face the same barriers and challenges. The article first details what specific health issues have to be dealt with in rural areas. The case of emergency care in Vermont is then developed to illustrate what could be the benefits of using ICTs to improve access to care.